Atelier 84 (Paris : Musée d'Art moderne de la Ville de Paris, 1984)
Agid, Olivier ; Aoun, Arezki ; Aulagnier, Daniel ; Boué, François ; Brandely, Daniel ; Cognée, Philippe ; Dalbis, Eric ; Guillon, Frank ; Jammes, Louis ; Krauth, Jean Marie ; Philippe Lamy ; Lévêque, Claude ; Mencoboni, Didier ; Mercier, Elisabeth ; Mosner, Ricardo ; Paysant, Michel ; Pierre et Gilles ; Ryan, David ; Seckler, Serge ; Sicilia, José Maria ; Taolouarn, Patrick ; Vidéo Clips
Atelier 84, Musée d'Art moderne de la Ville de Paris, 21 mars - 29 avril 1984
boek